Islamic religiosity, depression and anxiety among Muslim cancer patients - Ahmad Basri, Nadzirah; Gan, Chun Hong; Ng, Lai Oon; Kumagai, Shuzo (The International Academic Forum (IAFOR), 2015)
Active religious practice is central to Muslim livelihood. Among Muslims, this religious engagement is rarely studied with regards to its association in coping with critical illnesses. This study investigated the association between Islamic religiosity with depression and anxiety in Muslim cancer patients. Fifty-nine cancer patients recruited from a Malaysian public hospital and a cancer support group completed the Muslim Religiosity and Personality Inventory, Beck Depression Inventory and Beck Anxiety Inventory in July and August 2010. Islamic religiosity score, obtained from the sum of subscale scores of Islamic worldview and religious personality represents a greater understanding and practice of Islam in a comprehensive manner. Results yielded a significant negative correlation between Islamic religiosity score with both depression and anxiety. Depression was also found to be negatively associated with religious personality subscale. Older patients scored significantly higher on both Islamic worldview and religious personality whereas patients with higher education scored higher on Islamic worldview. Married patients scored significantly higher scores on religious personality than the single patients. Results provided an insight into the significant role of religious intervention which has huge potentials to improve the psychological health of cancer patients particularly Muslims in Malaysia. Research implication includes the call for professionals to meet the spiritual needs of Muslim cancer patients and incorporating religious components in their treatment, especially in palliative care.